Implementación de bancos forrajeros de especies leñosas de matarratón (gliricidia sepium), caraca (erythrina poeppigiana) y botón de oro (tithonia diversifolia), en el Cantón La Mana, parroquia Guasaganda. - Noboa Acurio, Johan Moisés (2022)
A forage bank is an area within the farm in which one or several forage species are established, which can be perennial or annual cycle due to the need to maintain good quality forage. It was established on the Emiliano farm in the Guasaganda parish in a essay whose objectives were to implement fodder banks with three species, mataraton (Gliricidia sepium), caraca (Erythrina poeppigiana), buttercup (Tithonia diversifolia), evaluate the agronomic characteristics of these species and determine the chemical composition. For this, plots of 3.00 m long and 1.50 m wide were established with six repetitions for each forage plant and a total of 360 plants, the design used was the randomized complete block design (DBCA), the Tukey's significance test at 5% probability, the variables were: percentage of catch (%); number of branches, forage production (g) per plant, chemical composition at foliar and bromatological level. The best results were recorded in the buttercup forage with 86.83% harvest, number of branches 18.67; 87.50 g of biomass per plant and in the foliar part nitrogen stood out at 45 and 60 days with 2.75 and 3.50%.